Fuzzy Smart Reward for Serious Game Activity Design - Haryanto, Hanny; Rosyidah, Umi; Kardianawati, Acun; Astuti, Erna Zuni; Dolphina, Erlin; Haryanto, Ronny (Scientific Journal of Informatics, 2023)
Purpose:  Serious game has been widely considered to be a potential learning tool, due to its main advantage to provide a fun experience in learning. The experience is supported mainly by in-game activities, where feedback is given in the form of rewards. However, rewards often don't work well due to various factors, for example, rewards are always the same, so they are monotonous. We use Appreciative Learning as underlying concept for activity design and fuzzy logic to create the reward behavior, called Fuzzy Smart Reward.Methods: We use Appreciative Learning as underlying concept for activity design and fuzzy logic to create the reward behavior. Appreciative Learning activities consists of Discovery, Dream, Design and Destiny. We propose fuzzy-based smart reward for those activities. The smart reward takes player achievement in each activity as input for the fuzzy inference system and give the dynamic reward as output.Result: A game prototype is developed as a test subject. The result shows that the smart reward could dynamically adjust the reward based on game conditions and player performance. Test conducted using Game Experience Questionnaire get the score 3.3 out of 4.Novelty:  There aren't many studies on dynamic rewards in structured reward systems; the majority of studies remove dynamic rewards from reward systems. In our research, a "smart reward" is a dynamic reward in a structured reward system that is created using artificial intelligence and is based on activities for appreciative learning. The use of Fuzzy Logic for structured reward behavior is also very rare.